Kinerja Dinas Pariwisata Dalam Melakukan Pengawasan Terhadap Jasa Akomodasi Pariwisata Villa Di Kabupaten Badung - Gusti Ayu Putu Dina Aryani; Putu Nomy Yasintha; Komang Adi Sastra Wijaya (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2021)
The rapid development of tourism in Badung Regency has caused it provision of tourism accommodation has increased particularly in villa accommodation. However, there are villas that are already operating but do not have business legality, therefore it is necessary to carry out strict supervision to prevent violations. The purpose of this study was to determine the performance of the Tourism Office in Supervising of Villa Tourism Accommodation in Badung Regency. The theory used is Mahsun's Theory of Performance which includes Input, Process, Output, Outcome, Benefit, and Impact. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation study. The results showed that the Performance of the Tourism Office in Supervision of Villa Tourism Accommodation has been running well but has not been optimal because there are still obstacles, namely limited human resources, narrow monitoring targets and the absence of strict sanctions given.